COMPETITIVENESS THEORY - Rudianto, Y. Lilik (Program Doktor Ilmu Ekonomi, 2009)
The objectives of this paper is to assess the basis of competitiveness theory. It also discusses the origin of the concept of competitiveness. The term ‘competitiveness’ is an interesting term, and numerous definitions and explanations have been implemented in research. This categorization can be in the form of personal competitiveness by individual companies, at the microeconomic level where economic sectors and industries view with each other, and at the level of macroeconomics where national economies compete. The term relates generally to market economic matters, but it can also be considered to comprise three distinct divisions, which are the competitiveness of companies (microeconomic level), competitiveness of industries (mezzo- economic level), and competitiveness of national economies (macroeconomic level). According to unit of analysis of competitiveness, there are Nation State Competitiveness, Firm Competitiveness and Individual Competitiveness. There are also world competitiveness and SMEs Competitiveness. The last part review small and medium enterprise competitiveness, globalization, and the link between entrepreneurship and competitiveness. Keywords: World Competitiveness, Nation State Competitiveness, Firm Competitiveness, Individual Competitiveness, SMEs Competitiveness.